2018
DOI: 10.3390/ijms19030909
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Metabolism and Transport Mechanisms as Potential Antifungal Targets

Abstract: Discovering new drugs for treatment of invasive fungal infections is an enduring challenge. There are only three major classes of antifungal agents, and no new class has been introduced into clinical practice in more than a decade. However, recent advances in our understanding of the fungal life cycle, functional genomics, proteomics, and gene mapping have enabled the identification of new drug targets to treat these potentially deadly infections. In this paper, we examine amino acid transport mechanisms and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 86 publications
0
27
0
Order By: Relevance
“…Another option would be targeting or exploiting fungal amino acid transport mechanisms. A current review of this strategy can be found here [109].…”
Section: Amino Acid Metabolism As a Potential Drug Targetmentioning
confidence: 99%
“…Another option would be targeting or exploiting fungal amino acid transport mechanisms. A current review of this strategy can be found here [109].…”
Section: Amino Acid Metabolism As a Potential Drug Targetmentioning
confidence: 99%
“…More focused studies are needed to find which mechanism is involved in differential metabolites having amino acids, lipids, fatty acids, tricarboxylic acid (TCA) cycle, purines, starch and sucrose were observed in both PiCB-treated and control mycelia (Table S1 and Figure 4). Amino acids are the important nutritional source for the P. digitatum, and their metabolic pathways may be targeted to check the fungal growth [33,34]. Among the 23 amino acids detected in P. digitatum mycelia, 18 amino acids were increased, while five amino acids were significantly decreased in PiCB-treated samples compared with the respective controls (Table S1 and Figure 4).…”
Section: Effects Of Picb On the Metabolic Profiles Of P Digitatum Mymentioning
confidence: 99%
“…Among these ligands, Sadenosyl-L-methionine is used for a therapeutic against depression, liver disorders, fibromyalgia, and osteoarthritis [64], but also is an authentic substrate for this enzyme. Sinefungin is a natural drug produced by Streptomyces griseolus and experimentally used as antibiotics [65][66][67] (Fig. 3A).…”
Section: '-O-ribose Methyltransferasementioning
confidence: 99%